2020
DOI: 10.3390/nu12123673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yeast Mannan Which Promotes Beneficial Bacteroides on the Intestinal Environment and Skin Condition: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Yeast mannan (YM) is an indigestible water-soluble polysaccharide of the yeast cell wall. In vitro fecal fermentation studies showed that YM could exhibit a notable prebiotic effect. The aim of this randomized, double-blind, placebo-controlled study was to assess the efficacy of YM intake on the intestinal environment and skin condition. One hundred and ten healthy female subjects aged 30–49 years were supplemented with YM or placebo for eight weeks. Skin dryness was set as the primary endpoint. No side effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Bacteroides was the only genera with average relative abundance higher than 5% that was modulated by MedDiet. Bacteroides includes potentially beneficial species that could promote mucosal colonization, enforce the epithelial barrier of the gut, and have anti-inflammatory properties [ 58 , 59 ]. All other modulated taxa had a relative abundance lower than 5%, an observation similar to what was reported after 7 days of antibiotics [ 28 ], which further supports the idea that many microbiota modulators affect lower abundance taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides was the only genera with average relative abundance higher than 5% that was modulated by MedDiet. Bacteroides includes potentially beneficial species that could promote mucosal colonization, enforce the epithelial barrier of the gut, and have anti-inflammatory properties [ 58 , 59 ]. All other modulated taxa had a relative abundance lower than 5%, an observation similar to what was reported after 7 days of antibiotics [ 28 ], which further supports the idea that many microbiota modulators affect lower abundance taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Mannan polysaccharides, recognized as innate immune stimulants, bolster both non-specific and targeted immune responses [ 33 ]. Documented to exhibit potent antiviral immunity [ 34 ], they can also decrease gastrointestinal tryptophan and serotonin levels, improving the gut environment [ 35 ]. Thus, the efficacy of SJP in mitigating alcoholic hepatic impairments in zebrafish larvae seems inferior to LJP.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical application of prebiotics has received increasing attention because of their low risk of serious side effects, ease of administration, and high potential to influence the composition and function of intestinal microbiota. We previously found that yeast mannan (YM) promotes the growth of specific Bacteroides in both in vitro and in vivo studies [ 7 , 8 , 9 ]. YM is a soluble, indigestible carbohydrate originating from the yeast cell walls and consists of highly branched mannose polymers with molecular weights ranging from 20 to 200 kDa [ 10 ].…”
Section: Introductionmentioning
confidence: 99%